Assessment of basal heave stability for deep excavation - Agung, Alexander (2013)
In this study, PLAXIS finite element software with shear strength reduction method (SSR) will be used and plane strain (2-dimensional) model will be applied to examine the parameters that affect the stability of braced excavation in clays. The parameters considered are thickness of the soft clay layer underlying the hard stratum (T), wall penetration below the base of excavation (D) and the stiffness of the wall (EI). Only deep excavations, with excavation width less than the final excavation depth are considered.